The Paradoxical Perception of Religious Leaders and Community Members About Islam Nusantara - Fahmi, Reza; Aswirna, Prima; Nurdin, Syafruddin (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2019)
This article aims to describe the prejudices of religious leaders and community members about Islam Nusantara. This study also aims to draw the picture of people’s preconceptions about Islam Nusantara and to connect the bigotry of religious leaders, the community, and its relation to the social conflict of the people of Padang. The study employes qualitative and quantitative approaches (mixing methods). The population in this study is 32 religious leaders and 168 community members. Data collection techniques employed are observation, interview, and psychological scale. The sampling method used is a simple random sampling technique. This article employed the Pearson correlation as the data analysis techniques. The results of this study found that generally the negative prejudices of religious leaders about Islam Nusantara were high. At the same time, the social conflict during society is classified as low. Meanwhile, the correlation aspect shows that there is no significant correlation between the views of religious leaders and community members about Islam Nusantara, and social conflict in society.